A controlled CO2 release experiment in a fault zone at the In-Situ Laboratory in Western Australia. (August 2020) - Michael, Karsten; Avijegon, Arsham; Ricard, Ludovic; Myers, Matt; Tertyshnikov, Konstantin; Pevzner, Roman; Strand, Julian; Hortle, Allison; Stalker, Linda; Pervukhina, Marina; Harris, Brett; Feitz, Andrew; et al.
Highlights: Enduring research facility for developing M&V technologies for secure underground storage. Unique controlled-release experiment injecting 38 t of CO2 into a fault zone. Injection of CO2 at 340 m depth fills gap between shallow release and storage field trials. Accumulation of as low as 7 t of CO2 was detected with fibre optics and seismic. Abstract: A controlled-release test at the In-Situ Laboratory Project in Western Australia injected 38 tonnes of gaseous CO2 between 336−342 m depth in a fault zone, and the gas was monitored by a wide range of downhole and surface monitoring technologies. Injection of CO2 at this depth fills the gap between shallow release (<25 m) and storage (>600 m) field trials. The main objectives of the controlled-release test were to assess the monitorability of shallow CO2 accumulations, and to investigate the impacts of a fault zone on CO2 migration. CO2 arrival was detected by distributed temperature sensing at the monitoring well (7 m away) after approximately 1.5 days and an injection volume of 5 tonnes. The CO2 plume was detected also by borehole seismic and electric resistivity imaging. The detection of significantly less than 38 tonnes of CO2 in the shallow subsurface demonstrates rapid and sensitive monitorability of potential leaks in the overburden of a commercial-scale storage project, prior to reaching shallow groundwater, soil zones or the atmosphere. Observations suggest that the fault zone did not alter the CO2 migration along bedding at the scale and depth of the test. Contrary to model predictions, no vertical CO2 migration was detected beyond the perforated injection interval. CO2 and formation water escaped to the surface through the monitoring well at the end of the experiment due to unexpected damage to the well's fibreglass casing. The well was successfully remediated without impact to the environment and the site is ready for future experiments.